Hepatic Dysfunction in Hospitalized Patients with Acute Thyrotoxicosis: A Decade of Experience. (29th November 2012) - Elias, Richard M.; Dean, Diana S.; Barsness, Gregory W.
Abstract : Thyroid disease is a common condition, and thyroid hormone excess or deficiency is known to have wide-ranging effects on a variety of organ systems. Our objective is to describe the magnitude, biochemical features, and clinical characteristics of hepatic abnormalities in patients with acute thyrotoxicosis. We performed a retrospective review of all patients admitted to our institution between January 1, 1998 and December 31, 2008 with a discharge diagnosis of acute thyrotoxicosis excluding iatrogenic causes. The records of these patients were reviewed and data extracted regarding demographic, biochemical, and clinical data particularly relevant to liver function. Fourteen patients were identified of which eleven had liver studies performed. The majority (90.9%) had Graves disease. Nine of eleven patients (81.8%) had some degree of hepatic abnormality. Seven patients (63.6%) had an elevation in one or both transaminases, and two (18.2%) had isolated synthetic dysfunction as manifested as an elevated INR and/or decreased albumin without transaminitis. The mean magnitude of deviation from the normal range was greater in the transaminases as compared to bilirubin, INR, or albumin. Definitive treatment was radioiodine ablation in six cases (54.5%) and surgical thyroidectomy in two cases (18.2%). Noniatrogenic acute thyrotoxicosis requiring hospitalization is a rare condition which is most frequently caused by Graves disease. The majority of patients have disordered liver tests of a highly variable nature, making the recognition of this association important in the care of patients presenting with acute thyrotoxicosis.